Percepção dos usuários sobre a implantação e funcionalidade de uma nova ciclovia na cidade de Cascavel-PR - Brassal, Vitor Augusto (2018)
The relation between environmental pollution and the usage of automobiles has widen discussions concerning the usage of alternate ways of transportation, especially the non-motorized, in which the bicycle is a viable and efficient alternative. Therefore, it is vital to know the profile of people using bicycle, their motivation, difficulties, and necessities to thus contribute with subsidies for public policy about urban mobility. With this objective, was investigated the profile of cyclists and their perceptions regarding the implementation and functionality of a new bicycle path on Brasil Avenue in Cascavel/PR. Moreover, was determined the impact of the path implementation in people mobility, and their opinions regarding the use of the bicycle path. In addition, was perceived the opinion of key-informants - representatives of public policy and related with the paths system project – with the objective of understand the knowledge of this professionals related with urban mobility. Was used a quali-quantitative mixed methodology with both quantitative and qualitative aspects applying data collection as follow: i) area of study delimitation; ii) determination of sampling effort; iii) application of a quiz to 219 cyclists; and 4) interviews with the five key-informants. The main results show that the majority of the bicycle path users were male (84%), between 21 and 40 years old (51%), with an income of two minimum-wage salaries (29%) and medium educational level (28%). Most people use the bicycle path for physical activities, although many uses it as a way to work (36%). Most (74%) agree that the bicycle path brought an increase in bicycle usage as transportation been a good investment for the municipality (77%). More than half of the users utilize bicycle every day (51%) and 37% do not own a car. Most of the cyclists ( 71%) practice other sports beside cycling, and not due to medical recommendation (90%). More than half of the cyclists interviewed (52%) rode through all Brasil Avenue’s bicycle path extension, and most (76%) claimed fell safer about accidents while riding on the path rather than on the street. Most of cyclists (41%) believed that respect on traffic and improvements on the infrastructure are the most important factors to improve the city’s bicycle path system. Considering the public service perspective, the interviews showed a good understand about the importance of urban mobility and alternative ways of transportation, as bicycles. In general, was observed that the necessities pointed out by the cyclists are understood by the public service and they were incorporated in paths system project. Was concluded that the Brasil Avenue bicycle path was approved by the population by allowing to the cyclists an exclusive space, safe, and comfortable, that have been attracting new users. Thus, the city of Cascavel is inserted in the global tendency when search to develop a more sustainable city.